DRUG UTILIZATION PATTERN OF ANTIHYPERTENSIVE MEDICATIONS IN A TERTIARY CARE HOSPITAL, SOUTH INDIA - ANURADHA VP; C, MUHAS; SRUTHY S, ANJALI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study is to assess drug use pattern of antihypertensive medications in hypertensive patients. Methods: It is a prospective cross-sectional study conducted in the outpatient dispensary, Government Medical College, Thiruvananthapuram for the period of 6 months from January 2019 to June 2019. About 500 prescriptions of patients visiting outpatient dispensary with an antihypertensive prescription were enrolled for the study. Drug use patterns of different classes of antihypertensive medications were analyzed from individual prescriptions. Results: A total of 500 patients were included in this study, among which 281 were male (56.2%) and 219 (43.8%) were female. In 500 patients, 133 patients were treated with monotherapy. In that 42.1% of patients were treated with amlodipine, 28.57% of patients were treated with losartan. In combination therapy most commonly used was double therapy (42.8%) followed by triple therapy (24.2%). Calcium Channel Blockers (56.2%) was most prescribed class of drug followed by Angiotensin Receptor Blockers. Conclusion: This study reveals that calcium channel blockers as most prescribed class of antihypertensive and Amlodipine was the most prescribed antihypertensive. In our study, most of the patients were treated with combination therapy in that double drug therapy was most common. There is a chance of various medication errors, development of adverse drug reaction as majority (290) of patients belong to age above 60 and chances of getting error also increases as combination therapy is most used. Therefore close monitoring is required for such patients.